Obstetric and gynecologic ultrasound curriculum and competency assessment in residency training programs: consensus report. (3rd January 2018) - Abuhamad, A.; Minton, K. K.; Benson, C. B.; Chudleigh, T.; Crites, L.; Doubilet, P. M.; Driggers, R.; Lee, W.; Mann, K. V.; Perez, J. J.; Rose, N. C.; Simpson, L. L.; et al.
ABSTRACT: Ultrasound imaging has become integral to the practice of obstetrics and gynecology. With increasing educational demands and limited hours in residency programs, dedicated time for training and achieving competency in ultrasound has diminished substantially. The American Institute of Ultrasound in Medicine assembled a multi‐Society Task Force to develop a consensus‐based, standardized curriculum and competency assessment tools for obstetric and gynecologic ultrasound training in residency programs. The curriculum and competency‐assessment tools were developed based on existing national and international guidelines for the performance of obstetric and gynecologic ultrasound examinations and thus are intended to represent the minimum requirement for such training. By expert consensus, the curriculum was developed for each year of training, criteria for each competency assessment image were generated, the pass score was established at or close to 75% for each, and obtaining a set of five ultrasound images with pass score in each was deemed necessary for attaining each competency. Given the current lack of substantial data on competency assessment in ultrasound training, the Task Force expects that the criteria set forth in this document will evolve with time. The Task Force also encourages use of ultrasound simulation in residency training and expects that simulation will play a significant part in the curriculum and the competency‐assessment process. Incorporating this training curriculum and the competency‐assessment tools may promote consistency in training and competency assessment, thus enhancing the performance and diagnostic accuracy of ultrasound examination in obstetrics and gynecology. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.